P44 Maintenance of space for COPD (A Self-management Programme of Activity, Coping & Education): a six month qualitative study. (14th November 2013) - Apps, LD; Harrison, SL; Mitchell, KE; Steiner, M; Morgan, M; Singh, SJ; Singh, SJ
Abstract : Introduction & Objectives: Few self-management interventions for COPD have conducted qualitative interviews on completion of such a programme and none have followed participant's longer term. This study conducted interviews with participants allocated to the SPACE FOR COPD self-management programme as part of an RCT. We aimed to gain insight into how the programme was utilised over a 6 month period. Earlier analysis of interviews carried out at 6 weeks highlighted the value of the education material 1 . Method: Semi-structured interviews were carried out with participants (n = 24) receiving SPACE for COPD six months after receiving the intervention. Interviews were transcribed verbatim and a constant comparison approach was taken to analysis supported by NVivo software (Version 10) by 2 researchers with experience in qualitative methods. Results: Following preliminary analysis, four main themes describe the challenges and conducive behaviours that influenced participant's self-management behaviours during 6 months of using SPACE FOR COPD - continuing to utilise the manual, establishing an exercise routine, social support & multiple burdens. Many participants describe continuing to use the SPACE FOR COPD manual (e.g. for breathing control techniques and to refresh memory) and establishing an exercise routine early on with the intervention. Social support was utilised for informational (advice), instrumental (help with tasks) and emotional reasons and largely consisted of family members. Challenges to continued regular exercise at home included barriers of time and weather and wider ranging burdens (e.g. other family member's ill-health, life events, such as moving house). Conclusion: Participants reported continued use of the manual and acknowledged thatestablishing a regular exercise routine was instrumental to encouraging continued exercise and this behaviour may have increased feelings of personal control over their disease.However, the challenges identified could disrupt these patterns of self management and further healthcare professional support may be required to help participants cope with these. Participants viewed the telephone support they had had favourably. References: L Apps, S Harrison, J Williams, M Steiner, M Morgan & S Singh. (2012). A self-management programme of activity, coping & education (SPACE) for COPD: Patients perspective. ERS Annual Conference 2012